Factors affecting job satisfaction of workers in indonesian construction companies - Marzuki, Puti Farida; Permadi, Hestiyani; Sunaryo, Indryati (Journal of Civil Engineering and Management, 2012)
This paper describes the influence of job characteristics, rewards, relations with superiors, relations with co-workers, and fulfillment of higher order needs, as job facets, on the job satisfaction of workers in Indonesian construction companies. A questionnaire survey was conducted in Jakarta (the capital city) and Bandung (one of Indonesia’s major cities). The results revealed that workers in different occupational groups and managerial positions perceive differently the conditions of job facets and that there are different levels of job satisfaction among different categories of workers. This research indicates that workers care about the quality of their work and company’s performance and that these aspects affect significantly their job satisfaction. Reward is also revealed to have an important influence on workers’ job satisfaction.